The Black Colleges - Amburgey, Lillian ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
The establishment and growth of black colleges in the United States is traced from a catechizing school in New York City in 1704 to the present day. After a brief historical review, statistics are given in contemporary colleges, students, accreditation, and location. Problems facing the institutions and students are addressed and the future assessed. Positive forces operating to assist them in surviving are outlined, including federal support and scholarship programs. Some recommendations are offered for maintaining and strengthening existing institutions, dealing with library facilities, financial support, curricula changes, tuition fees, and admissions policy. (LBH)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accreditation (Institutions); Admission Criteria; Black Colleges; Black Education; Black Students; College Libraries; Curriculum Development; Federal Aid; Financial Needs; Higher Education; History; Private Colleges; School Statistics; Statistical Data; Tuition; Reports, Research